An intelligent integrated approach of Jaya optimization algorithm and neuro-fuzzy network to model the natural convection in an open round cavity. (3rd March 2020) - Akbari, E.; Karami, A.; Nazari, S.; Ashjaee, M.
ABSTRACT: An intelligent integrated approach of Jaya optimization algorithm and neuro-fuzzy network is introduced to model the natural convection in an open round cavity against the decision parameters. The decision parameters are the Rayleigh number (Ra) in range of 10 5 to 2 × 10 5 and ratio of the nonconductor barrier distance from the bottom of the cavity to the cavity diameter (H/D) in range of 0 to ∞. After that, the obtained hybrid model is applied to forecast the average Nusselt number in the cavity. In the next step, the experimentally obtained data by using a Mach–Zehnder interferometer is utilized to train the hybrid model. The accuracy of the hybrid model is evaluated through the calculation of average testing and checking errors. According to the obtained results, there is an optimum ratio (H/D = 0.5), in which the heat transfer is maximum. Moreover, it was found that the best hybrid model forecasts the natural convection in the cavity with the mean absolute percentage error of less than 0.75% and 1.40% for the testing and checking data, respectively.